2021
DOI: 10.3390/ijerph18105324
|View full text |Cite
|
Sign up to set email alerts
|

“Despite the Differences, We Were All the Same”. Group Cohesion in Diagnosis-Specific and Transdiagnostic CBT Groups for Anxiety and Depression: A Qualitative Study

Abstract: Group cohesion refers to a sense of belonging, mutual support and identification with other group members. Group cohesion has been associated with better outcomes, lower drop-out rates, more interpersonal support and better participation in psychotherapy. Nevertheless, the role of group cohesion in CBT has not yet received much attention. The rationale for delivering CBT in groups is that patients can model themselves through each other due to their similarities in symptoms. However, there has recently been a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Interestingly, ambivalent feelings related to terminating therapy may not be exclusive to BPD patients. In a recent qualitative study of patients' experience of transdiagnostic CBT for patients with anxiety disorder and depression (25), also found this. This could indicate that ambivalent feelings at termination may be more of a general phenomenon rather than a diagnosis specific or therapy specific.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, ambivalent feelings related to terminating therapy may not be exclusive to BPD patients. In a recent qualitative study of patients' experience of transdiagnostic CBT for patients with anxiety disorder and depression (25), also found this. This could indicate that ambivalent feelings at termination may be more of a general phenomenon rather than a diagnosis specific or therapy specific.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, a previous qualitative add‐on study to the TRACT trial showed that patients who felt safe in the group equated that with being willing to share in the group and trying out exposure exercises, which are considered key elements in the treatment (Bryde Christensen et al, 2021). Thus, the individual personality and the dynamic between personalities can influence patients' behaviours in group therapy and their participation in essential therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In the group therapy literature, group cohesion is found to be an important mechanism of change and for reducing dropout rates (Burlingame et al, 2018). In addition, group cohesion is found to promote greater motivation to attend sessions and complete homework assignments in CBT group therapies for anxiety and depression (Christensen et al, 2021). Group cohesion can be understood as the sense of belonging as well as the extent to which group members coordinate their efforts to achieve goals (American Psychological Association, 2023; Bryde Christensen et al, 2021).…”
Section: Course Of Treatmentmentioning
confidence: 99%